Analysis Of Factors Influencing The Use Of The Electronic Application Health Information System - Community Based Nutrition Reporting Recording (E-Ppgbm) In The Makassar City Health Office - Lamban, Adrita; Amir, Muhammad Yusran; Palutturi , Sukri; Darmawansyah,; Stang, (South Eastern European Journal of Public Health, 2024)
Until now, Indonesia is still facing nutritional problems. The three burdens of malnutrition currently faced include undernutrition, hidden hunger, and excess body weight. This condition has encouraged the Indonesian Ministry of Health to develop an electronic application information system for Community-Based Nutrition Reporting Recording (e-PPGBM). Makassar City has implemented the e-PPGBM information system, but until now, the level of user acceptance cannot be known because there is no related research. This study aims to analyze the factors that influence the use of the electronic Health Information System application - Community Based Nutrition Reporting Recording (e-PPGBM) in the Makassar City Health Service. This type of research is quantitative research namely analytical observational with a cross sectional study approach. The sample for this study used total sampling, namely all officers using the e-PPGBM application in 47 Community Health Centers. Data collection with a questionnaire using Google From. Processing uses the chi square test and logistic regression test. Based on the research results, it shows thatsystem use does not have a significant influence onbenefits/net benefitswith p value = 0.818≥0.05, user satisfaction has a significant influence onbenefits/net benefitswith p value = 0.009 <0.05, organizational structure does not have a significant influence onbenefits/net benefitswith p value = 0.525≥0.05, the organizational environment has a significant influence onbenefits/net benefitswith a value of p=0.003<0.05, system quality has a significant influence onbenefits/net benefitswith p value=0.006<0.05, information quality has a significant influence onbenefits/net benefitswith a value of p=0.001<0.05, service quality has a significant influence onbenefits/net benefitswith p value=0.005<0.05.